A Massively Parallel Algorithm for the Approximate Calculation of Inverse p-th Roots of Large Sparse Matrices - Lass, Michael; Mohr, Stephan; Wiebeler, Hendrik; Kühne, Thomas; Plessl, Christian (Proc. Platform for Advanced Scientific Computing (PASC) Conference)
We present the submatrix method, a highly parallelizable method for the approximate calculation of inverse p-th roots of large sparse symmetric matrices which are required in different scientific applications. Following the idea of Approximate Computing, we allow imprecision in the final result in order to utilize the sparsity of the input matrix and to allow massively parallel execution. For an n x n matrix, the proposed algorithm allows to distribute the calculations over n nodes with only little communication overhead. The result matrix exhibits the same sparsity pattern as the input matrix, allowing for efficient reuse of allocated data structures. We evaluate the algorithm with respect to the error that it introduces into calculated results, as well as its performance and scalability. We demonstrate that the error is relatively limited for well-conditioned matrices and that results are still valuable for error-resilient applications like preconditioning even for ill-conditioned matrices. We discuss the execution time and scaling of the algorithm on a theoretical level and present a distributed implementation of the algorithm using MPI and OpenMP. We demonstrate the scalability of this implementation by running it on a high-performance compute cluster comprised of 1024 CPU cores, showing a speedup of 665x compared to single-threaded execution.
Keywords: approximate computing; linear algebra; matrix inversion; matrix p-th roots; numeric algorithm; parallel computing

Automated Code Acceleration Targeting Heterogeneous OpenCL Devices - Riebler, Heinrich; Vaz, Gavin Francis; Kenter, Tobias; Plessl, Christian (Proc. ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming (PPoPP))
Keywords: htrop

Imaging of 180∘ ferroelectric domain walls in uniaxial ferroelectrics by confocal Raman spectroscopy: Unraveling the contrast mechanism - Rüsing, Michael; Neufeld, Sergej; Brockmeier, Julian; Eigner, Christof; Mackwitz, P.; Spychala, K.; Silberhorn, Christine; Schmidt, Wolf Gero; Berth, Gerhard; Zrenner, Artur; Sanna, S. (Physical Review Materials)
In recent years, Raman spectroscopy has been used to visualize and analyze ferroelectric domain structures. The technique makes use of the fact that the intensity or frequency of certain phonons is strongly influenced by the presence of domain walls. Although the method is used frequently, the underlying mechanism responsible for the changes in the spectra is not fully understood. This inhibits deeper analysis of domain structures based on this method. Two different models have been proposed. However, neither model completely explains all observations. In this work, we have systematically investigated domain walls in different scattering geometries with Raman spectroscopy in the common ferroelectric materials used in integrated optics, i.e., KTiOPO4, LiNbO3, and LiTaO3. Based on the two models, we can demonstrate that the observed contrast for domain walls is in fact based on two different effects. We can identify on the one hand microscopic changes at the domain wall, e.g., strain and electric fields, and on the other hand a macroscopic change of selection rules at the domain wall. While the macroscopic relaxation of selection rules can be explained by the directional dispersion of the phonons in agreement with previous propositions, the microscopic changes can be explained qualitatively in terms of a simplified atomistic model.

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

Das moralische Urteil von Schülerinnen und Schülern mit Verhaltensstörungen. Theoretische Ansätze und empirische Befunde aus kohlbergianischer und neo-kohlbergianischer Perspektive - Aschhoff-Hartmann, Stefanie

Erarbeitung von Konstruktionsregeln für Hybridbauteile: Integration von metallischen Einlegern in FDM-Strukturen - Schöppner, Volker; Knoop, F.; Köhler, M.; Lieneke, Tobias; Zimmer, Detmar (Konstruktion)

Additive Fertigung nach Maß - Schöppner, Volker; Zimmer, Detmar; Knoop, Frederick; Lieneke, Tobias (Kunststoffe)

Systematik zur integrativen Planung des Verhaltens selbstoptimierender Produktionssysteme - Köchling, Daniel

Das Praxissemester fachdidaktisch in den Blick nehmen - Wosnitza, Christopher; Caruso, Carina; Vogelsang, Christoph (die hochschullehre)
In vielen Bundesländern ist ein Praxissemester obligatorischer Bestandteil der Lehramtsausbildung. Zunehmend wird untersucht, ob und in welcher Form Studierende die für diesen Ausbildungsabschnitt vorgesehenen Standards erreichen. Dabei fokussieren Untersuchungen primär bildungswissenschaftliche Kompetenzbereiche. Die Frage, inwiefern das Praxissemester zum Erwerb domänenspezifischer bzw. insbesondere fachdidaktischer Kompetenzen beiträgt, lässt sich als Forschungsdesiderat konstatieren. Es ist zudem unklar, wie bestimmte Lerngelegenheiten diesen Prozess beeinflussen. Um diesem Forschungsbedarf zu begegnen, wurde an der Universität Paderborn die interdisziplinäre Forschungsgruppe Fachdidaktische Forschung im Praxissemester gegründet. Ziel der gemeinsamen Arbeit ist es, auf Basis wissenschaftlicher Ergebnisse einen Beitrag zur Weiterentwicklung des Praxissemesters zu leisten. Am Praxissemester sind drei Ausbildungsorte beteiligt: Hochschulen, Zentren für schulpraktische Lehrerausbildung (ZfsL) und Schulen. Ein Schwerpunkt liegt daher auf der Untersuchung des kritisch-produktiven Verhältnisses von Hochschullehre und Praxis. Vor dem Hintergrund fachübergreifender Heuristiken zur Professionalisierung in der Lehrer/innenbildung, werden in diesem Artikel aktuelle Projekte der Forschungsgruppe und deren Kontexte vorgestellt und diskutiert.
Keywords: Praxissemester; Lehrer/innenbildung; Evaluation; Kompetenzentwicklung; Fachdidaktik / school internships; teacher education; evaluation; professional competence; subject matter education

Physikdidaktische Forschung in der Hochschule. Eine Übersicht über Forschungsdesigns & -methoden - Woitkowski, David; Vogelsang, Christoph (die hochschullehre)

Fully-differential, DC-coupled, Self-biased, Monolithically-integrated Optical Receiver in 0.25μm Photonic BiCMOS Technology for Multi-channel Fiber Links - Gudyriev, Sergiy; Scheytt, Christoph; Yan, Lei; Christian, Meuer; Zimmermann, Lars (IEEE Bipolar/BiCMOS Circuits and Technology Meeting)
A fully-differential receiver structure for fiber links is presented, in which the photodiode (PD) is DC-coupled to the transimpedance amplifier (TIA) and biased through the feedback resistors. The biasing voltage is defined by the internal structure of the input stage. Different options are suggested that allow to adjust PD biasing. Multiple architecture variants are proposed, that were implemented in 0.25μm SiGe BiCMOS technology. Initial measurement results are reported, proving the feasibility of the concept. A 25Gbps hybrid receiver designed to comply with a specific standard is also presented, featuring large horizontal eye opening of 800mV, OMA of -15dBm at BER of 10 -6 and power dissipation of 330mW from a single 3.3V power supply.

Silicon Photonics Microsystems for Communications and Sensing - Scheytt, Christoph (W3+Fair on Optoelectronics, Electronics, and Mechanics)

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Enhanced columnar mesophase range through distortions in arene cores - Vollbrecht, Joachim; Wiebeler, Christian; Schumacher, Stefan; Bock, Harald; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)

Wann ist eine Unterrichtsplanung 'gut'? - Planungsperformanz in Praxisratgebern zur Unterrichtsplanung - Vogelsang, Christoph; Riese, Josef (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status Quo und Perspektiven aus Sicht der empirischen Forschung.)

Wie valide sind Professionswissenstests?: Zum Zusammenhang von erfasstem Wissen, Unterrichtshandeln und Unterrichtserfolg - Cauet, Eva; Vogelsang, Christoph (Professionelle Kompetenz von Lehrkräften der Chemie und Physik)

Analyse und Optimierung der Delta-Alpha-Problematik im Fertigungsprozess von asymmetrischen hybriden Werkstoffen aus Metall und faserverstärkten Kunststoffen - Frantz, Meike Maria
Die Bedeutung von beanspruchungsangepassten Bauteilen aus metallischer Grundstruktur verstärkt mit einem Faserverbundkunststoff (FVK) steigt im automobilen Leichtbau stark an. Ein Verfahren zur Herstellung dieser hybriden Strukturen ist das Prepreg-Pressen. Bei diesem Verfahren wird der FVK direkt unter Temperatur und Druck auf die metallische Grundstruktur geklebt, wobei es aufgrund der deutlich unterschiedlichen Wärmeausdehnungskoeffizienten zu starken Eigenspannungen im Bauteil kommt. Diese prozessinduzierten Eigenspannungen wurden im Rahmen dieser Arbeit reduziert. Dazu wurde in einem ersten Schritt die Ausgangslage untersucht, indem die Eigenspannungen analytisch berechnet sowie experimentell untersucht wurden. Im zweiten Schritt wurde ein Konzept zur Reduzierung dieser erarbeitet. Hierbei spielt vor allem die Temperaturverteilung im Bauteil eine entscheidende Rolle, die analytisch, numerisch sowie praktisch bestimmt wurde. Im Anschluss wurden die Parameter dieses angepassten Verfahrens optimiert. In weiteren Optimierungsschritten wurde der Einfluss unterschiedlicher Materialien auf die induzierten Eigenspannungen sowie auf die mechanischen Eigenschaften des Gesamtverbundes untersucht. Die Eigenspannungen konnten mithilfe des optimierten Verfahrens deutlich reduziert werden. Abschließend wurden die Ergebnisse in einer Methodik zur Herstellung eigenspannungsoptimierter asymmetrischer Hybride zusammengefasst.

Liquid crystals and precious metal: from nanoparticle dispersions to functional plasmonic nanostructures - Atorf, Bernhard; Funck, Timon; Hegmann, Torsten; Kempter, Susanne; Liedl, Tim; Martens, Kevin; Mühlenbernd, Holger; Zentgraf, Thomas; Zhang, Bingru; Kitzerow, Heinz-Siegfried; Urbanski, Martin (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Ferroelectric Liquid Crystals in Microcapillaries: Observation of Different Electro-optic Switching Mechanisms - Knust, Steffen; Wahle, Markus; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Electroluminescent and Optoelectronic Properties of OLEDs with Bay-Extended, Distorted Perylene Esters as Emitter Materials - Vollbrecht, Joachim; Blazy, Simon; Dierks, Philipp; Peurifoy, Samuel; Bock, Harald; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

MULTIDIMENSIONAL STOCHASTIC MATERIAL MODELING AT LARGE DEFORMATIONS CONSIDERING PARAMETER CORRELATIONS - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Proceedings of the 2nd International Conference on Uncertainty Quantification in Computational Sciences and Engineering (UNCECOMP 2017))

(n)- AND (n + 1)-LAYERED COMPOSITE SPHERE MODELS FOR THERMO-CHEMO-MECHANICAL EFFECTIVE PROPERTIES - Mahnken, Rolf; Dammann, Christian; Lenz, Peter (International Journal for Multiscale Computational Engineering)

Thermo-chemo-mechanical Effective Properties for Homogeneous and Heterogeneous n -Phase Mixtures with Application to Curing - Dammann, Christian; Lenz, Peter; Mahnken, Rolf (Procedia CIRP)

Thermo-Mechanical Simulation of Hard Turning with Macroscopic Models - Uhlmann, E.; Mahnken, Rolf; Ivanov, I. M.; Cheng, C. (Lecture Notes in Production Engineering)

Plasmonic nanostructures: spectroscopy and electron microscopy - Kitzerow, Heinz-Siegfried; Lindner, Jörg

Tunable plasmonic structures utilizing liquid crystals - Atorf, B.; Rasouli, H.; Rennerich, R.; Muhlenbernd, H.; Reineke, B. J.; Zentgraf, T.; Kitzerow, Heinz-Siegfried (2017 11th International Congress on Engineered Materials Platforms for Novel Wave Phenomena (Metamaterials))

Liquid crystal medium and liquid crystal display - Wilkes, D.; Wittek, M.; Hoischen, A.; Kitzerow, Heinz-Siegfried; Nordendorf, G.; Schmidtke, J.

Die Nutzung institutioneller Lerngelegenheiten und die Entwicklung bildungswissenschaftlichen Wissens angehender Lehrkräfte. - Christina, Watson; Seifert, Andreas; Schaper, Niclas (Zeitschrift für Erziehungswissenschaften)

Unterrichtsplanung im Fach Geschichte – Modellierung und Erfassung geschichtsdidaktischen Planungswissens von Lehramtsstudierenden - Wolf, Jörgen; Seiffert, Joana; Seifert, Andreas; Rothland, Martin; Brauch, Nicola (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status und Perspektiven aus der Sicht der empirischen Forschung.)

Studienerfolg als der Erwerb bildungswissenschaftlichen Wissens vs. Studienerfolg als Veränderung der Kompetenzselbsteinschätzungen: Entwicklungen im Praxissemester. - Seifert, Andreas (Gemeinsame Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie)

Analytical competence of teachers: modelling and validating a core construct. - Scholl, Daniel; Seifert, Andreas; Krepf, Matthias; Plöger, Wilfried (Congress “New International Perspectives on Future Teacher’s Professional Compe-tencies”)

Neue Herausforderungen für Zentren für Lehrerbildung. - Schaper, NIclas; Festner, Dagmar; Seifert, Andreas; Watson, Christina; Hilligus, Annegret Helen (10. Bundeskongress der Zentren für Lehrerbildung.)

Test-Development to Assess Future History Teacher’s PCK. - Brauch, Nicola; Wolf, Jörgen; Seiffert, Joana; Seifert, Andreas; Rothland, Martin (17th Biennial EARLI Conference)

BMBF-Tagung: Bildungsforschung 2020: Interdisziplinäre und interinstitutionelle Po-tenziale eines Veranstaltungsformats. - Schütz, Julia; Seifert, Andreas (Der Pädagogische Blick)

Kompetenzselbsteinschätzungen und bildungswissenschaftliches Wissen im Lehramtsstudium – Zeigen sich Unterschiede zwischen einem Orientierungspraktikum und dem Praxissemester? - Festner, Dagmar; Gröschner, Alexander; Seifert, Andreas (2. Internationalen Kongress „Lernen in der Praxis.“)

Learning to Practice (LtP): Ermittlung der Kompetenzentwicklung im Praxissemester – Pädagogisches Wissen und Kompetenzeinschätzungen. - Seifert, Andreas; Schaper, Niclas; König, JOhannes (Vortrag auf dem NRW-Netzwerktreffen Lehrerbildung 2017)

Die Befragungen im bildungswissenschaftlichen Studium an der Universität Paderborn: Ansatz, Ergebnisse, Implikationen, Verbesserungsmöglichkeiten. - Seifert, Andreas (Forschungskolloquium der Psychologie)

Bright nanoscale source of deterministic entangled photon pairs violating Bell's inequality, - Jöns, Klaus D.; Schweickert, L; Versteegh, M.A.M; Dalacu, D; Poole, P.J; Gulinatti, A; Giudice, A; Zwiller, V; Reimer, M.E

On-chip single photon filtering and multiplexing in hybrid quantum photonic circuits - Elshaari, A.W; Esmaeil Zadeh, I; Fognini, A; Reimer, M. E; Dalacu, D; Poole, P.J; Zwiller, V; Jöns, Klaus D.

Crystal phase quantum well emission with digital control - Assali, S; Lähnemann, J; Vu, T.T.T; Jöns, Klaus D.; Gagliano, L; Verheijen, M.A; Akopian,, N; Bakkers, E.P.A.M; Haverkort, J,E.M

Phonon-assisted two-photon interference from remote quantum emitters - Reindl, M; Jöns, Klaus D.; Schubert, David; Schimpf, C; Y Huo, Y; Zwiller, V; Trotta, R; Rastelli,, A

Two-photon interference from two blinking quantum emitters - Jöns, Klaus D.; Stensson, K; Reindl, M; Swillo, M; Huo, Y; Zwiller, V; Rastelli, A; Trotta, R; Björk, G

Semiconductor devices for entangled photon pair generation: a review - Orieux, A; Versteegh, M.A.M; Jöns, Klaus D.; Ducci, S

Integrierte, selbstoptimierende Fahrdynamikregelung mit Einzelradaktorik - Reinold, Peter

Bloch oscillations and resonant radiation of light propagating in arrays of nonlinear fibers with high-order dispersion - Yulin, A.; Driben, R.; Meier, Torsten (Physical Review A)

Anisotropic excitons and their contributions to shift current transients in bulk GaAs - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Physical Review B)

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Modified two-photon interference achieved by the manipulation of entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Physical Review A)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Organic Thin-Film Transistors for AMOLED Applications - Meyers, Th.; Vollbrecht, J.; Vidor, F.; Reker, J.; Kitzerow, Heinz-Siegfried; Hilleringmann, Ulrich (IEEE Xplore, MikroSystemTechnik 2017)

High-Resolution Two-Dimensional Optical Spectroscopy of Electron Spins - Salewski, M.; Poltavtsev, S. V.; Yugova, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Akimov, I. A.; Meier, Torsten; Bayer, M. (Physical Review X)

Towards integrated superconducting detectors on lithium niobate waveguides - Höpker, Jan Philipp; Bartnick, Moritz; Meyer-Scott, Evan; Thiele, Frederik; Meier, Torsten; Bartley, Tim; Krapick, Stephan; Montaut, Nicola M.; Santandrea, Matteo; Herrmann, Harald; Lengeling, Sebastian; Ricken, Raimund; et al. (Quantum Photonic Devices)

A microscopic approach to ultrafast near band gap photocurrents in bulk semiconductors - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXI)

Damping of Rabi oscillations in intensity-dependent photon echoes from exciton complexes in a CdTe/(Cd,Mg)Te single quantum well - Poltavtsev, S. V.; Reichelt, Matthias; Akimov, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Meier, Torsten; Bayer, M. (Physical Review B)

Bloch oscillations sustained by nonlinearity - Driben, R.; Konotop, V. V.; Meier, Torsten; Yulin, A. V. (Scientific Reports)

Investigation of Residual Stress in Laser Transmission Welding of Polypropylene - Schöppner, Volker; Lakemeyer, P.; Wübbeke, Andrea; Geißler, S.; Schmidt, M. (70th Annual Assembly of the International Institute of Welding (IIW))

Effective meso properties for fibre reinforced polymer curing - Mahnken, Rolf

Increasing process speed in the laser melting process of Ti6Al4V and the reduction of pores during hot isostatic pressing - Ahlers, Dominik; Koppa, Peter; Hengsbach, F.; Gloetter, P.; Altmann, A.; Schaper, Mirko; Tröster, Thomas (Proceedings of the 28th Annual InternationalSolid Freeform Fabrication Symposium – An Additive Manufacturing Conference)

Shear edge tests: a benchmark in investigating the influence of different surface pretreatment methods on the shear stress of intrinsically manufactured metal-CFRP hybrids - Weidenmann, Kay André; Pottmeyer, Florentin; Wang, Zheng; Tröster, Thomas; Meiners, Dieter; Zinn, Carolin; Schaper, Mirko; Gonzalez, Jonathan Serna (International Journal of Automotive Composites)

Fully-Differential, Hybrid, Multi-channel 4x25Gbps Direct Direction Receiver in 0.25\textmum BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Kress, Christian; Yan, Lei; Christian, Meuer; Zimmermann, Lars (OSA Frontiers in Optics + Laser Science)
A hybrid multi-channel receiver featuring fully-differential transimpedance input stages for 25Gbps data rate per channel is presented along with measurement results focusing on the channel-to-channel interference and sensitivity. OMA of -16dBm at a BER of 10−4 is estimated at the photodiode for all channels. Each channel dissipates 330mW of power provided from a single 3.3V supply voltage.

Efficient Branch and Bound on FPGAs Using Work Stealing and Instance-Specific Designs - Riebler, Heinrich; Lass, Michael; Mittendorf, Robert; Löcke, Thomas; Plessl, Christian (ACM Transactions on Reconfigurable Technology and Systems (TRETS))
Branch and bound (B&B) algorithms structure the search space as a tree and eliminate infeasible solutions early by pruning subtrees that cannot lead to a valid or optimal solution. Custom hardware designs significantly accelerate the execution of these algorithms. In this article, we demonstrate a high-performance B&B implementation on FPGAs. First, we identify general elements of B&B algorithms and describe their implementation as a finite state machine. Then, we introduce workers that autonomously cooperate using work stealing to allow parallel execution and full utilization of the target FPGA. Finally, we explore advantages of instance-specific designs that target a specific problem instance to improve performance. We evaluate our concepts by applying them to a branch and bound problem, the reconstruction of corrupted AES keys obtained from cold-boot attacks. The evaluation shows that our work stealing approach is scalable with the available resources and provides speedups proportional to the number of workers. Instance-specific designs allow us to achieve an overall speedup of 47 × compared to the fastest implementation of AES key reconstruction so far. Finally, we demonstrate how instance-specific designs can be generated just-in-time such that the provided speedups outweigh the additional time required for design synthesis.
Keywords: coldboot

Flexible FPGA design for FDTD using OpenCL - Kenter, Tobias; Förstner, Jens; Plessl, Christian (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Compared to classical HDL designs, generating FPGA with high-level synthesis from an OpenCL specification promises easier exploration of different design alternatives and, through ready-to-use infrastructure and common abstractions for host and memory interfaces, easier portability between different FPGA families. In this work, we evaluate the extent of this promise. To this end, we present a parameterized FDTD implementation for photonic microcavity simulations. Our design can trade-off different forms of parallelism and works for two independent OpenCL-based FPGA design flows. Hence, we can target FPGAs from different vendors and different FPGA families. We describe how we used pre-processor macros to achieve this flexibility and to work around different shortcomings of the current tools. Choosing the right design configurations, we are able to present two extremely competitive solutions for very different FPGA targets, reaching up to 172 GFLOPS sustained performance. With the portability and flexibility demonstrated, code developers not only avoid vendor lock-in, but can even make best use of real trade-offs between different architectures.
Keywords: tet_topic_hpc

High-Throughput and Low-Latency Network Communication with NetIO - Schumacher, Jörn; Plessl, Christian; Vandelli, Wainer (Journal of Physics: Conference Series)

Betriebsorganisation - Schneider, Martin; Wilke, Christian Manfred; Iseke, Anja (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)

Impact of carbon-ion implantation on the nonlinear optical susceptibility of LiNbO3 - Spychala, Kai J.; Berth, Gerhard; Widhalm, Alex; Rüsing, Michael; Wang, Lei; Sanna, Simone; Zrenner, Artur (OPTICS EXPRESS)
In this work we study the impact of ion implantation on the nonlinear optical properties in MgO:LiNbO3 via confocal second-harmonic microscopy. In detail, we spatially characterize the nonlinear susceptibility in carbon-ion implanted lithium niobate planar waveguides for different implantation energies and fluences, as well as the effect of annealing. In a further step, a computational simulation is used to calculate the implantation range of carbon-ions and the corresponding defect density distribution. A comparison between the simulation and the experimental data indicates that the depth profile of the second-order effective nonlinear coefficient is directly connected to the defect density that is induced by the ion irradiation. Furthermore it can be demonstrated that the annealing treatment partially recovers the second-order optical susceptibility.

Erweiterung des Portfolios presshärtbarer Stähle durch gezielte Werkstoff- und Prozessmodifikationen - Marten, Thorsten

Classical and quantum resonances for hyperbolic surfaces - Guillarmou, Colin; Hilgert, Joachim; Weich, Tobias (Mathematische Annalen)
Keywords: General Mathematics

Systematik zur Erarbeitung modellbasierter Entwicklungsaufträge - Echterhoff, Olga

Entwurfssystematik für den präventiven Schutz Intelligenter Technischer Systeme vor Produktpiraterie - Kliewe, Daniel

Indikatorbasierte Erkennung und Kompensation von ungenauen und unvollständig beschriebenen Softwareanforderungen - Baeumer, Frederik Simon

Systematik für eine prototypenbasierte Entwicklung mechatronischer Systeme in der Technologie MID (Molded Interconnect Devices - Jürgenhake, Christoph

Low-Power, Ultra-compact, Fully-differential 40Gbps Direct Detection Receiver in 0.25μm Photonic BiCMOS SiGe Technology - Gudyriev, Sergiy; Scheytt, Christoph; Meister, Stefan; Knoll, Dieter; Lischke, Stefan; Zimmermann, Lars; Meuer, Christian (IEEE Group IV Photonics Conference)
Recently electronic-photonic integrated circuits (EPIC) technology platforms became available [1] which allow fabrication of very compact and fast monolithic receivers. However, although the cointegration of electronics and photonics on the same chip allows for novel circuit topologies which could help to improve circuit performance quite often transmitter and receiver circuit design is using more or less conventional approaches. We propose a novel architecture that effectively utilizes the benefits of the EPIC technology such as: very short interconnects between the photodiode and the amplifier, symmetrical and compact photodiode structure with low operating voltages. Our architecture shown in Fig. 1 features fully-differential input stage, automatic biasing of the photodiode, DC coupling between diode and transimpedance amplifier (TIA) and very small footprint.

Recent Advances in Millimeter-Wave-and Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Microelectronics Seminar)

Electronic-Photonic System-On-Chip - Scheytt, Christoph (DFG Rundgespräch:"Disruptive system concepts using electronic-photonic integration)

Bay-Extended, Distorted Perylene Esters Showing Visible Luminescence after Ultraviolet Excitation: Photophysical and Electrochemical Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Neuba, Adam; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

ProfiLe-P+ – Professional Competence in Academic Physics Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Fischer, Hans; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst

Einsatz der Widerstandserwärmung bei hydraulischen Schneidgeräten zum Trennen von hochfesten Stahlwerkstoffen in Kraftfahrzeugen - Siewers, Bernd
Die zunehmend eingesetzten hochfesten Stähle im Automobilbau können zu schwerwiegenden Problemen bei Verkehrsunfällen führen, da hydraulische Schneidgeräte zur Befreiung von Personen an ihre mechanischen Grenzen geraten. Ein Ansatz zur Behebung dieses Problems kann die Widerstandserwärmung der zu schneidenden Werkstoffe sein. Im Rahmen dieser Dissertation wurde durch Werkstoffuntersuchungen ermittelt, dass die hochfesten Stähle einen starken Abfall der Festigkeit aufweisen, während bei denselben Temperaturen potentielle Schneidwerkstoffe deutlich höhere Festigkeiten besitzen. Das Konzept wurde schließlich in einem Funktionsmuster umgesetzt. Schneidversuche zeigten, dass durch die Widerstandserwärmung ein deutlicher Abfall der erforderlichen Schneidkraft erreicht werden konnte. Insgesamt konnte gezeigt werden, dass die Widerstandserwärmung ein vielversprechendes Konzept darstellt, um hochfeste Karosseriestähle zuverlässig und schnell zu durchtrennen und somit die Befreiung eingeschlossener Fahrzeuginsassen zu gewährleisten.
Keywords: Leichtbau; Hybridsysteme; Werkstoffe

A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor - Mahnken, Rolf; Caylak, Ismail; Dridger, Alex (A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor)
This paper presents a numerical method for solution of a stochastic partial differential equation (SPDE) for a linear elastic body with stochastic coefficients (random variables and/or random fields). To this end the stochastic finite element method (SFEM) is employed, which uses W IENER’S polynomial chaos expansion in order to decompose the coefficients into deterministic and stochastic parts. As a special case, we consider isotropic material behavior with two fluctuating parameters. Computational approaches involving GALERKIN projection are applied to reduce the SPDE into a system of deterministic PDEs. Furthermore, we consider normally distributed random variables, which are assumed to be stochastically independent, and which establish the number of stochastic dimensions. Subsequently, the resulting finite element equation is solved iteratively. Finally, in a representative example for a plate with a ring hole we study the influence of different variances for material parameters on the variances for the finite element results.

Modeling of variant-interaction during bainitic phase transformation - Ehlenbröker, Ulrich; Mahnken, Rolf; Petersmann, M; Antretter, T (IOP Conference Series: Materials Science and Engineering)

Extension of a multi-mechanism model: Hardness-based flow and transformation induced plasticity for austenitization - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Macromodelling of Transformation Induced Plasticity combined with Viscoplasticity for Low-Alloy Steels - Schneidt, Andreas; Mahnken, Rolf (steel research international)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase Ginzburg-Landau/Cahn-Hilliard systems for simulation of lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (Archive of Applied Mechanics)

A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

The concept of generalized stresses for computational manufacturing and beyond - Mahnken, Rolf; Cheng, Chun; Düsing, Martin; Ehlenbröker, Ulrich; Leismann, Thorben (GAMM-Mitteilungen)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Temperature-insensitive electro-optic response of polymer-stabilized blue phases - Nordendorf, Gaby; Schmidtke, Jürgen; Wilkes, David; Kitzerow, Heinz-Siegfried (Journal of Materials Chemistry C)
Polymer-stabilized blue phase liquid crystal in-plane switching cell.
Keywords: Materials Chemistry; General Chemistry

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry